Managing Noncompliance through Health Education (So-cratic Method) among Families with A History of Hyper-tensionat the Bergas Community Health Center - Olif Rina Susanti; Wulansari Wulansari (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Nonadherence refers to the behavior of an individual or family that does not follow the treatment plan recommended by healthcare professionals. This behavior can reduce treatment effectiveness, hinder disease control, and increase the risk of complications, especially in chronic conditions such as hypertension. Appropriate nursing management is therefore necessary to improve family understanding, awareness, and involvement in following the prescribed treatment plan. This scientific paper aims to describe the man-agement of nonadherence through health education using the Socratic method among a family with a history of hypertension at the Bergas Community Health Center. The study employed a descriptive method with a case study design and applied a family nursing process approach. The nursing process consisted of assessment, formulation of nursing diagnoses, planning of interventions, implementation of nursing ac-tions, and evaluation. The sampling technique used was non-probability sampling, with one family selected as the study subject. Health education using the Socratic method was delivered through guided questions and dialogue to explore the family’s understanding of hypertension and treatment adherence. The case study focused on how this educational approach was incorporated into family nursing care to address nonadherence while maintaining continuity between assessment findings, interventions, implementation, and evaluation of the nursing process.